2013
DOI: 10.4103/0973-1075.116701
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes towards organ donation among people seeking healthcare in tertiary care centers of coastal south India

Abstract: Background:Organ transplantation is the most preferred treatment modality for end-stage organ diseases. The need for the transplants is higher than the availability. Prerequisites for the success of transplantation program include awareness and positive attitudes.Aim:To assess the perceptions and attitudes of the people seeking health care in tertiary care centers towards organ donation in Mangalore, India.Settings and Design:This cross-sectional study included 863 people seeking general healthcare as outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 5 publications
10
73
2
Order By: Relevance
“…Other similar studies have shown that 60%–80% of the study participants agreed to the same. [102728] Among the medical students in our study, 56.8% of them also agreed with the same, and this was also supported by another study conducted in the southern part of India. [13] This shows the attitude of the study participants on consent for organ donation from the family members and also the importance of gaining family's permission before retrieval.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other similar studies have shown that 60%–80% of the study participants agreed to the same. [102728] Among the medical students in our study, 56.8% of them also agreed with the same, and this was also supported by another study conducted in the southern part of India. [13] This shows the attitude of the study participants on consent for organ donation from the family members and also the importance of gaining family's permission before retrieval.…”
Section: Discussionsupporting
confidence: 87%
“…[1013] This could have been attributed due to the differences of opinion from various religious groups, which has been proved in other studies. [272930] The median score for the statement on willingness to donate their organs was higher (4 [4–5]) in our study [Table 3] similar to studies;[1011132831] however, further questions were not asked if they have signed an organ donor card which could have informed us about their practice.…”
Section: Discussionsupporting
confidence: 73%
“…This study also reported that knowledge and age were not significantly associated (5). The study carried out by Mithra P et.al showed that 59.6% of the participants expressed willingness to donate organs (4).…”
Section: Discussionmentioning
confidence: 99%
“…In India, despite the Transplant of Human Organs Act (THO), neither has the commerce stopped nor have the number of deceased donors increased to take care of organ shortage [2]. The studies carried out in India stresses the importance of increased public awareness on the need for deceased donor organs [3,4,5 ]. Problems and mortality among people with kidney disease are increasing that necessitates the importance of finding the knowledge and attitude of adults about kidney donation.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant parts (80.6%) of members in our investigation knew about organ gift and these discoveries are like those of past studies. 5,17,18 The examination populace said positive reaction for their own particular organ to be given. This finding was more obvious and it was considerably higher than the discoveries from a study, where 19.3% respondents showed them not willing to be living organ contributors.…”
Section: Discussionmentioning
confidence: 99%